Lontara Piezoelectric Paving Block as an Eco-Innovation Project in STEAM-PJBL Green Chemistry Learning: A Systematic Literature Review on Science Literacy and Environmental Awareness - A. Muthmainnah; Eda Lolo Allo; Dewiyanti Fadly (IAIN Sorong, 2026)
The low science literacy of Indonesian students and the lack of environmental awareness remain urgent challenges in 21st-century science education. Indonesia consistently ranks among the lowest in PISA and TIMSS assessments, while environmental degradation from plastic waste and used engine oil continues to escalate. This systematic literature review aims to identify the scientific foundation and potential of developing a Green Chemistry-based STEAM Eco-Innovation Module through Project-Based Learning (PjBL) as an innovative learning framework capable of simultaneously enhancing students' science literacy and environmental awareness at the senior secondary (SMA/SMK) level. The review was conducted through a systematic review of recent peer-reviewed literature, supplemented by additional sources focusing on engineering aspects. Four major findings emerged: (1) the STEAM-PjBL approach is empirically proven to significantly improve science literacy and 21st-century skills; (2) the integration of green chemistry principles into learning modules effectively cultivates environmental awareness; (3) the utilization of PET/HDPE plastic waste, wood sawdust, and used engine oil as paving block raw materials has been experimentally validated, including B3 hazardous waste encapsulation engineering and controlled thermal melting processes; and (4) road-based piezoelectric technology can successfully convert pedestrian kinetic energy into clean electrical energy. The Lontara Piezoelectric Paving Block innovation integrates the local Bugis-Makassar cultural identity (Lontara script) with cutting-edge green eco-innovation technology. Three critical research gaps were identified: the absence of a locally contextualized green chemistry-based STEAM module in Indonesia, the limited integration of waste management and renewable energy harvesting into a single learning module, and the scarcity of studies specifically measuring environmental awareness as an outcome of STEAM-PjBL interventions at the SMA/SMK level.